2020
DOI: 10.13057/biodiv/d220135
|View full text |Cite
|
Sign up to set email alerts
|

Richness and diversity of insect pollinators in various habitats around Bogani Nani Wartabone National Park, North Sulawesi, Indonesia

Abstract: Abstract. Koneri R, Nangoy MJ, Wakhid. 2021. Richness and diversity of insect pollinators in various habitats around Bogani Nani Wartabone National Park, North Sulawesi, Indonesia. Biodiversitas 22: 288-297.  The pollination of plants by insects is one of the most important and essential ecosystem services in natural and agricultural landscapes and Insect pollinators play an important role in this process. This is because they help to transfer pollen from the anther to the stigma, which leads to fertilization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Coffee flowers near the forest were more frequently visited by Apis cerana, while coffee flowers far from the forest were more commonly visited by Stomorhina discolor. This occurred because the forest edge offers nesting sites for insect pollinators, particularly bees (Koneri et al 2021). Saturni et al (2016) also asserted that natural habitats such as forests provide food and nesting resources for insect pollinators.…”
Section: Discussionmentioning
confidence: 99%
“…Coffee flowers near the forest were more frequently visited by Apis cerana, while coffee flowers far from the forest were more commonly visited by Stomorhina discolor. This occurred because the forest edge offers nesting sites for insect pollinators, particularly bees (Koneri et al 2021). Saturni et al (2016) also asserted that natural habitats such as forests provide food and nesting resources for insect pollinators.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of phytoplankton was analyzed using the formula: E= c × A/fa × V; where: E = phytoplankton density (ind/ltr), c = total observed individuals, A = phytoplankton concentrate volume, fa = phytoplankton sample volume, and V = sample volume (Clesceri et al, 1989). The species diversity index (Shannon-Wiener diversity (H'), the species evenness index (Pielou evenness (J) and the correlation between species abundance, number of species, diversity index, and species evenness index with chlorine content were analyzed using Paleontological Statistics software (PAST software v. 2.12) (Koneri et al, 2021).…”
Section: Figure 1 Research Frameworkmentioning
confidence: 99%
“…In Bungo Tanjung Sepakat and Saiyo, the two pollinators collected were Drosophilidae (Diptera) and Formicidae (Hymenoptera), while the pollinator collected in Manunggang Sakato was Formicidae (Table 4). Several studies have reported that Hymenoptera is an order of insect pollinators mostly found and dominant in all habitat types (Siregar et al 2016;Bashir et al 2019;Koneri et al 2021). The presence of pollinating insects is strongly influenced by the availability of flowering plants in their habitat.…”
Section: Role Of Insectsmentioning
confidence: 99%
“…The presence of pollinating insects is strongly influenced by the availability of flowering plants in their habitat. The reduction in flowering plants led to a decrease in pollinating insect species (Koneri et al 2021). According to Bailey et al (2014), insect pollinators are thermophilous, they prefer warm open areas to forage and also travel further out into the field to forage in open areas as well.…”
Section: Role Of Insectsmentioning
confidence: 99%